Variability in the chemical composition of triticale grain, flour and bread. (September 2016) - Fraś, Anna; Gołębiewska, Kinga; Gołębiewski, Damian; Mańkowski, Dariusz R.; Boros, Danuta; Szecówka, Przemysław
Abstract: During the last few decades triticale has become a commercial crop grown in a variety of environmental conditions worldwide. Triticale, a hybrid cereal developed by crossing wheat and rye combines the valuable properties of both parental forms. In the present study the differences in chemical composition between grain, flour and bread of eight triticale varieties were determined. The results were compared against the standard wheat variety. Independently of the degree of material processing, all samples were characterised for nutrients (protein, starch, ash, lipids) and bioactive components (dietary fibre (DF), total polyphenols (TPC)) and viscosity of water extracts (WEV). Following grain milling, the average content of some components decreased significantly in comparison to grain (protein (2%), ash (58%), lipids (38%), DF (64%), TPC (40%)). After baking the differences in the content of some bread components were compared to flour. The most significant differences between flour and bread samples were noted in the average content of ash (0.8% vs. 2.3%), starch (74.1% vs. 64.7%), DF (4.6% vs. 5.4%), TPC (0.9mgGAE/g vs. 0.5mgGAE/g). Our results show that the grain of some modern triticale varieties, with a favourable chemical composition from a technological and nutritional perspective, is good material for flour and bread production. Highlights: Triticale varieties showed significant variability in the content of all components. The milling process affected the nutrients and bioactive components of flour. The chemical composition of bread changed significantly compared to flour. There were similar relations in chemical composition between grain, flour and bread. Some triticale varieties are good material for flour and bread production.